Assessing the Technological Effects of Modernization, Renewal, and Consolidation Project for Rice Fields (Case Study: Gharetoghan Rural District, Neka Township) - Khadija Bozarjomehri; Elahe Anzaei (جغرافیا و پایداری محیط)
Examining stable agriculture and itۥs sub-systems is essential for obtaining more knowledge and information about these systems’ situation and, consequently, designing appropriate strategies and programs in moving towards stable agriculture. The main goal of this study is to examine the technological effects of modernization, renewal and consolidation of rice fields and to assess its success in terms of the above-mentioned criteria based on farmers and experts’ viewpoints. The statistical community of this research consists of two groups. The first group includes 9 villages from Gharetoghan located in central part of Neka which have undergone the mentioned project. The other group consists of the experts that the project is directly performed by them or they were responsible in the performed project. The data was collected through field study and questionnaire distributed among the 260 farmers of the area understudy and 68 experts. The findings show that there is a correlation between the farmers and experts in the effectiveness of the project in terms of technological aspect. The correlation coefficients of technological aspect are 0/641 respectively.